Chondroitin sulfate-capped super-paramagnetic iron oxide nanoparticles as potential carriers of doxorubicin hydrochloride. (20th October 2016) - Mallick, Neha; Anwar, Mohammed; Asfer, Mohammed; Mehdi, Syed Hassan; Rizvi, Mohammed Moshahid Alam; Panda, Amulya Kumar; Talegaonkar, Sushama; Ahmad, Farhan Jalees
Highlights: A facile, one-pot green synthesis method was used. Chondroitin sulfate (CS) was an efficient capping agent for synthesis of SPIONs. CS interacted with iron oxide via bidentate chelation. DOX was entrapped onto the nanocarriers by electrostatic interaction with CS. IC50 value was decreased for DOX-loaded SPIONs than plain DOX. Abstract: Chondroitin-4-sulfate (CS), a glycosaminoglycan, was used to prepare CS-capped super-paramagnetic iron oxide nanoparticles, which were further employed for loading a water-soluble chemotherapeutic agent (doxorubicin hydrochloride, DOX). CS-capped SPIONs have potential biomedical application in cancer targeting. The optimized formulation had a hydrodynamic size of 91.2 ± 0.8 nm (PDI; 0.228 ± 0.004) and zeta potential of −49.1 ± 1.66 mV. DOX was loaded onto the formulation up to 2% (w/w) by physical interaction with CS. TEM showed nano-sized particles having a core-shell structure. XRD confirmed crystal phase of iron oxide. FT-IR conceived the interaction of iron oxide with CS as bidentate chelation and also confirmed DOX loading. Vibration sample magnetometry confirmed super-paramagnetic nature of nanoparticles, with saturation magnetization of 0.238 emu g −1 . In vitro release profile at pH 7.4 showed that 96.67% of DOX was released within 24 h (first order kinetics). MTT assay in MCF7 cells showed significantly higher (p < 0.0001) cytotoxicity for DOX in SPIONs than DOX solution (IC50 values 6.294 ± 0.4169 and 11.316 ± 0.1102 μg mL −1, respectively).